2017
DOI: 10.1073/pnas.1617981114
|View full text |Cite
|
Sign up to set email alerts
|

SM protein Munc18-2 facilitates transition of Syntaxin 11-mediated lipid mixing to complete fusion for T-lymphocyte cytotoxicity

Abstract: The atypical lipid-anchored Syntaxin 11 (STX11) and its binding partner, the Sec/Munc (SM) protein Munc18-2, facilitate cytolytic granule release by cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells. Patients carrying mutations in these genes develop familial hemophagocytic lymphohistiocytosis, a primary immunodeficiency characterized by impaired lytic granule exocytosis. However, whether a SNARE such as STX11, which lacks a transmembrane domain, can support membrane fusion in vivo is uncertain, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 69 publications
4
35
1
Order By: Relevance
“…STX4 siRNA‐treated cells exhibited over 60% reduction in target cell‐killing activity compared with those treated with NT‐siRNAs (Figure C). The reduction in cytotoxic activity of STX4 knockdown cells was comparable to the STX11 siRNA‐treated cells, which were previously shown to have reduced killing activity because of impairment in LG exocytosis (Figure C). On the contrary, STX3 siRNA‐treated cells, which also exhibited almost a 70% reduction in protein expression levels (Figure D), showed a slight increase in cytotoxic activity compared with NT siRNA‐treated cells (Figure C).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…STX4 siRNA‐treated cells exhibited over 60% reduction in target cell‐killing activity compared with those treated with NT‐siRNAs (Figure C). The reduction in cytotoxic activity of STX4 knockdown cells was comparable to the STX11 siRNA‐treated cells, which were previously shown to have reduced killing activity because of impairment in LG exocytosis (Figure C). On the contrary, STX3 siRNA‐treated cells, which also exhibited almost a 70% reduction in protein expression levels (Figure D), showed a slight increase in cytotoxic activity compared with NT siRNA‐treated cells (Figure C).…”
Section: Resultssupporting
confidence: 68%
“…CTLs express several syntaxins that belong to the PM Qa‐SNAREs sub‐group—STX3, STX4 and STX11 . Previous studies have shown that STX11, but not STX3 is required for CTL‐mediated cytotoxicity. However, it has not been investigated yet whether STX4 is also implicated in this pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the gene underlying FHL1 has not been identified, and mutations in the gene encoding the cytolytic effector perforin underlie FHL2, FHL3‐5 are due to mutations in genes encoding the machinery required for secretion of lytic granules, platelet alpha and dense granules and other regulated secretory organelles—specifically UNC13D (encoding munc13‐4, mutated in FHL3), STX11 (encoding syntaxin‐11, mutated in FHL4) and STXBP2 (encoding munc18‐2, mutated in FHL5). STX11 is a Qa SNARE that is part of the tSNARE complex at the plasma membrane required for cytolytic granule and platelet granule secretion . Munc18‐2 is a SM family member that specifically stabilizes STX11 in platelets and CTLs and is required for efficient STX11 expression at the plasma membrane and for granule fusion .…”
Section: Additional Disorders Of Lro Biogenesis Secretion and Motilitymentioning
confidence: 99%
“…Munc18‐2 is a SM family member that specifically stabilizes STX11 in platelets and CTLs and is required for efficient STX11 expression at the plasma membrane and for granule fusion . It is particularly critical to stabilize full fusion intermediates mediated by the lipid‐anchored STX11 . Consistent with its function, a number of FHL5 mutations disrupt the binding sites on munc18‐2 for STX11 or αSNAP or impede release of the N‐terminal STX11 peptide and thus block subsequent munc18‐2 function in facilitating SNARE complex assembly .…”
Section: Additional Disorders Of Lro Biogenesis Secretion and Motilitymentioning
confidence: 99%